Celebrity Endorsement in Advertising in the Context of Consumer Protection Law - Weronika WOZNA-BURDZIAK (Communications of International Proceedings, 2020)
There is a maxim repeated by goods and services providers in Poland which says that „advertising is the leverage of trade”. In market economy, new goods and services proliferate causing market expansion and increased competition. In such a challenging environment businesses have to strive to reach the target audient with their products and services. Therefore, advertising is ubiquitous in modern day society, and its volume is increasing dramatically worldwide. Whatever advertising media are used, it is undeniable that endorsement - which uses images or names of public figures or celebrities who command a high degree of trust or recognition to promote a product or service - increases the chance that a potential consumer will purchase the product advertised. Unsurprisingly, increasingly more businesses opt for celebrity endorsement as there is an undeniable appeal in a famous actress lending her image to a face cream or a famous footballer to a sneakers’ brand. However, from the perspective of consumer protection law, using celebrity endorsement in advertising is not so indisputable and arbitrary. Consumers are the weaker party of the legal relationship, and they are protected by the law not only the moment they enter into an agreement and after its conclusion, but also prior to that, which is why the use of celebrity endorsement is to some degree restricted. This paper explores the issue of celebrity endorsement in the context of consumer rights and consumer protection law on the basis of case studies exemplifying the presentation of medicinal products by celebrities or health professionals. The author applied a number of research methods, and focused mostly on the analysis of Polish regulations in the context of the legal doctrine and case law. The research methodology also includes references to consumer protection laws of other countries, an approach that enabled a comprehensive analysis of the subject.
Keywords: Consumer; Advertising; Consumer Protection; Image Advertising.